(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Explains the sensitive controversial stock verification as one of the occupational hazards and a post mortem, emphasizes need for clarity of objectives and procedures regarding stock verification and responsibilities of loss, points out that the cost of stock verification often far exceed the benefits, highlights norms and procedures of stock verification for Government of India institutions, discusses some advantages and various methods and procedures of physical verification, put forth precautionary measures to be taken against loss and mutilation of library documents, analyses the issue of responsibility of loss and ways of resolving the conflict of responsibility, presents the procedure for write-off of reasonable loss, finally concludes by stressing the need for rational and updated rules and procedures about stock verification, responsibility of loss and limits to write-off loss as well as vital role of professional bodies in this direction.